Penerapan Metode Waterfall pada Pengembangan Sistem Informasi Presensi - Difa Ayu Hespitasari; Atik Nurmasani; Azis Catur Laksono; Irma Rofni Wulandari (PPPM Institut Teknologi Pagar Alam, 2026)
The attendance system used in schools still uses a conventional system, that records attendance in a book. This system often encounters problems such as lost attendance books, which leads to data loss, difficulty tracking attendance data, and time-consuming monthly recaps. Furthermore, teachers and employees are often reluctant to record attendance because they have to write it in a book. Based on this, the author aims to help schools simplify the teacher and employee attendance process by creating a website-based online attendance information system. The method used in this study is the waterfall method, with stages of data collection, needs analysis, system design, coding, and system testing. Data collection produces information in the form of constraints and needs of teachers and employees. The analysis produces the focus of the business process to be developed, and functional requirements. The system design produces a database design and flow design in the form of use case diagrams and activity diagrams. Coding using the Code Igniter framework produces an information system display that is ready for use by users. System testing using the blackbox testing method produces information on the feasibility of features in the attendance information system. With this attendance information system, the attendance process for teachers and employees is easier to do compared to conventional systems